Efficacy of Internet-based cognitive behavioral therapy for reducing perfectionistic strivings in the Republic of Korea: A randomized controlled trial - Sanghoon Oh; Jeong hee Cha; Jungwon Joo; Ji Hyung Lee; Yunna Lee; Hyung Jun Lee; Dong Uk Yoon; Jeonghwan Lee (Internet Interventions, 2025)
Background: Perfectionistic strivings characterized by excessively high standards, fears of mistakes, and critical self-evaluations can lead to avoidance, worry, procrastination, and self-criticism, negatively impacting mental health. Since individuals with perfectionism are less likely to seek face-to-face therapy, internet-based cognitive behavioral therapy (ICBT) may improve accessibility. Objectives: This study evaluated the effectiveness of an ICBT program specifically designed to reduce perfectionistic strivings. Methods: A total of 101 participants with significant perfectionism were randomly assigned to a 5-week unguided ICBT program or a waiting list control group. Online assessments were conducted at baseline and post-intervention using the Frost Multidimensional Perfectionism Scale (FMPS), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), Perceived Stress Scale (PSS), and Satisfaction with Life Scale (SWLS). Intention-to-treat and completer analyses were performed. Results: Of 101 participants, 62 (61.4 %) completed both assessments. The ICBT group completed an average of 3.71 out of 5 modules, with 58.8 % completing all. Compared to the control group, the ICBT group showed significant reductions in perfectionistic strivings (FMPS Concern over Mistakes: d = −0.65, 95 % CI [−1.05, −0.25]), anxiety (GAD-7: d = −0.42, 95 % CI [−0.83, −0.01]), and increased life satisfaction (SWLS: d = 0.62, 95 % CI [0.20, 1.03]). Conclusions: The ICBT program effectively reduced perfectionistic strivings and related symptoms, highlighting its potential as a scalable and accessible intervention. Further studies are warranted to directly compare ICBT with traditional face-to-face CBT and assess the durability of treatment effects.